1975
DOI: 10.1247/csf.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic Study on DNA Synthesis in Lymphoid Tissues of the Rat Using Tritiated Thymidine and Deoxycytidine

Abstract: Labeling patterns with generally labeled tritiated deoxcytidine ([G-3H]dCyd) in lymphoid tissues were quite different from those labeled with tritiated thymidine ([methyl-3H]dThd). Thymic cortex and germinal centers of lymph node, spleen and Peyer's patch were labeled intensely with 3HdCyd but only a few lymphocytes in medulla of thymus and medullary cords of lymph node labeled with 3HdThd. The incorporation of 3HdThd into DNA was reduced significantly in the thymic cortex and germinal center of lymphoid tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Although mitotic analyses consistently reveal high rates of cell division in the thymic cortex and germinal centers of rats and mice (1,4,5,9,10), the cells in these areas are characterized by weak labeling with tritiated thymidine ([3H]TdR), whereas lymphocytes outside these anatomical regions of the same organs are labeled intensely with the same nucleoside (1, 6-10, 12, 18, 25). Recently, tritiated deoxycytidine ([3H]CdR) or radioiodine-labeled 5-iodo-2'-deoxyuridine has been used as a substitute for [3H]TdR to study lymphocyte production (1,2,12,14,(16)(17)(18)(19)(20)(21)23).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Although mitotic analyses consistently reveal high rates of cell division in the thymic cortex and germinal centers of rats and mice (1,4,5,9,10), the cells in these areas are characterized by weak labeling with tritiated thymidine ([3H]TdR), whereas lymphocytes outside these anatomical regions of the same organs are labeled intensely with the same nucleoside (1, 6-10, 12, 18, 25). Recently, tritiated deoxycytidine ([3H]CdR) or radioiodine-labeled 5-iodo-2'-deoxyuridine has been used as a substitute for [3H]TdR to study lymphocyte production (1,2,12,14,(16)(17)(18)(19)(20)(21)23).…”
mentioning
confidence: 99%
“…Recently, tritiated deoxycytidine ([3H]CdR) or radioiodine-labeled 5-iodo-2'-deoxyuridine has been used as a substitute for [3H]TdR to study lymphocyte production (1,2,12,14,(16)(17)(18)(19)(20)(21)23). Radioautographs revealed that lymphocytes in the thymic cortex and germinal centers were much more heavily labeled with generally tritiated deoxycytidine ([G-3H]CdR) than with [3H]TdR, whereas outside the germinal centers labeling was far more intense with [3H]TdR than with [G-3H]CdR (1,12,18). When rats were given nonradioactive CdR together with [3H]TdR, the weak labeling of cells in the thymic cortex and germinal centers decreased even further, whereas there was only slight reduction in the labeling intensity of cells in the thymic medulla and outside the germinal centers (1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of thymic lymphocytes (thymus cells), particularly those in the cortex, poorly label with [3H]thymidine (3HdThd) in vivo, although they rapidly divide (1,5,6,10). This has been attributed to the ability of these cells to utilize deoxycytidine (dCyd), which circulates in a considerable amount (8), for the formation of DNA-thymine (2,3,9).…”
mentioning
confidence: 99%